Enhancing livelihood security and local socio economic development through Mahatma Gandhi national rural employment guarantee scheme : an analysis - Punyavathi Jonna (Department of Agricultural Extension, College of Horticulture, 2012)
The Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) is widely appreciated as a unique attempt towards empowering rural poor through assured employment on demand. The programme guarantees at least 100days of wage employment in every fiscal year to the adult members of all households who volunteer to do unskilled manual labour at the minimum wage rate specified by the state government. MGNREGS which was initially launched in 200 districts was later extended to 130 districts. The scheme intends to use this man power for constructing productive assets and conserving natural resource with a view to facilitate agricultural production. Taking this into consideration, the study intended to find out the nature and extent of integration of MGNREGS with the agricultural development programmes implemented at the local level, the factors affecting planning, implementation and monitoring of MGNREGS as perceived by different stakeholders of the programme, demand side preference, supply side performance and assess the impact of MGNREGS on the livelihood security of beneficiaries. The study employed ex-post facto design based on the objectives. Out of twenty three districts, six districts were selected randomly. One Grama Panchayat from each district was selected randomly for the study. Five beneficiaries of MGNREGS, five implementing officers and five people’s representatives were randomly selected from each Grama Panchayat to make the sample size 90. .The final interview schedule was prepared by necessary modifications, additions and deletions based on pre-tested results. Percentages, paired ‘t’ test, Kendall’s coefficient of concordance and Mann-Whitney U Test were used for analyzing the data. The data were analyzed using Statistical Package for Social Science (SPSS). The study showed that there is perceptible difference in the extent of integration of different agricultural development programmes and their components with MGNREGS, across the six Grama Panchayats. Among 26 developmental programmes in the state, seven schemes are commonly integrated in all the six panchayats. While the implementing officers perceived institutional factors as most important in both planning and implementing stages, people’s representatives perceived managerial factors as most important in all stages of MGNREGS. The impact of MGNREGS on the livelihood security of beneficiaries was assessed based on the indices of direct as well as indirect changes. Employment generation and income generation- which reflected direct changes in livelihood security- were found to have increased as a result of implementation of the scheme. Distribution of beneficiaries based on indirect changes measured in terms of the ‘sense of empowerment’ showed that majority of respondents belong to medium category. While demand side preferences varied significantly across the grama panchayats, supply side performance did not vary too much. However, supply side performance indices were found to be lower than the corresponding demand side preference. Out of the several socio economic characteristics observed, age and caste were found to be significantly correlated negatively to income generated by the household. The study shows that MGNREGS has significantly enhanced the livelihood security of rural poor. However, integration of the programme with agricultural development is grossly inadequate in Andhra Pradesh. This suggests major policy shifts in the implementation of MGNREGS to make the programme effective. Unless local self government institutions are given enough authority to plan their own programmes, the quantum of employment generated would not be adequate to meet the demand. More components of the state sponsored and centrally sponsored schemes will have to be integrated with MGNREGS. The rural population should also be oriented to the provisions of the scheme to demand and avail more employment.